SENTIMENT ANALYSIS THROUGH SEARCH VOLUME INDEX ON BITCOIN VOLATILITY - Febri Rahadi; Sari Octavera (CV. Radja Publika, 2024)
This study aims to assess the link between investor sentiment, volatility, and Bitcoin return. Connections between the three are extremely intricate and diverse. Increasing search activity on Google Trends may presage a price increase, but it can also indicate heightened speculative sentiment or information saturation, potentially resulting in a price reduction. Volatility, while frequently seen negatively, may have a beneficial impact on Bitcoin's earnings by attracting risk-tolerant investors, stimulating trading activity, and facilitating hedging and arbitrage. However, volatility carries considerable risks, discouraging risk-averse investors, impeding institutional adoption, and impeding the practical use of Bitcoin as a means of exchange. Finally, the influence of SVI on investor mood and the volatility of Bitcoin returns is determined by a number of factors, including market sentiment, legislative changes, and technological advancements. As Bitcoin and its ecosystem continue to evolve, the nature of these interactions may shift.